Odpowiedź :
[tex]j)~~\sqrt[3]{27\cdot 64 \cdot 125} =\sqrt[3]{3^{3} \cdot 4^{3} \cdot 5^{3} } =\sqrt[3]{(3\cdot 4\cdot 5 )^{3} } =\sqrt[3]{60^{3} } =60^{3\cdot \frac{1}{3} } =60^{1} =60\\\\\\\k)~~\sqrt[3]{3^{6} \cdot 5^{3} \cdot 2^{9} } =\sqrt[3]{3^{6} }\cdot \sqrt[3]{ 5^{3} }\cdot \sqrt[3]{2^{9} } =3^{6\cdot \frac{1}{3} } \cdot 5^{3\cdot \frac{1}{3} } \cdot 2^{9\cdot \frac{1}{3} } =3^{2} \cdot 5^{1} \cdot 2^{3} =9\cdot 5\cdot 8=360[/tex]
[tex]l)~~\sqrt[3]{4^{9} \cdot 6^{3} \cdot 27} =\sqrt[3]{(4^{3} )^{3}\cdot 6^{3} \cdot 3^{3} } =\sqrt[3]{64^{3}\cdot 6^{3} \cdot 3^{3} } =\sqrt[3]{(64\cdot 6\cdot 3)^{3} } =\sqrt[3]{1152^{3} } =1152^{3\cdot \frac{1}{3} } =1152^{1} =1~152[/tex]
Korzystam ze wzorów:
[tex]\sqrt[n]{x^{n} } =x^{n\cdot \frac{1}{n} } =x^{1} =x\\\\(x^{n} )^{m} =x^{n\cdot m} \\\\x^{n} \cdot y^{n} =(x\cdot y)^{n} \\\\\sqrt[n]{x} =x^{\frac{1}{n} } \\\\\sqrt[n]{x\cdot y} =\sqrt[n]{x} \cdot \sqrt[n]{y}[/tex]